Cluster as place of efficient diffusion of knowledge. Experiences of Lower Silesia - Wachowska, Malgorzata (Managerial Economics, 2019)
Due to the fact that clusters should implement the idea of an open innovation model, the paper focuses on the role of Lower Silesian clusters in promoting knowledge flow between enterprises and other network participants, which are measured by the numbers of joint inventions and patent citations. On the basis of the analysis of national and international patent applications, it has been found that few inventions of enterprises are created in cooperation with other cluster members as well as that enterprises refer to the knowledge of other cluster members in their patent descriptions to a limited extent, which in general does not support the thesis that cluster membership contributes to the intensification of knowledge-diffusion processes.